Complications of Laparoscopy in Benign and Oncologic Gynecological Surgery - Worley, Michael J (MedReviews, LLC, 2009)
The evolution of laparoscopy from a diagnostic tool to a modality for major surgical procedures has been rapid and represents one of the most important surgical advancements in the past 30 years. Laparoscopy holds many advantages over laparotomy, including smaller surgical scars, faster recovery from surgery, and decreased time for return of bowel function. However, an appreciation of its potential complications is vital to patient care.